Ultrafast branching in the excited state of coumarin and umbelliferone - Krauter, Caroline M.; Möhring, Jens Markus; Buckup, Tiago; Pernpointner, Markus; Motzkus, Marcus (Physical chemistry, chemical physics, 2013)
In the present work we have explored the ultrafast relaxation network of coumarin and umbelliferone (7-hydroxy-coumarin) using time-resolved femtosecond spectroscopy and quantum chemical calculations. Despite the importance of the photophysical properties of coumarin derivatives for applications in biomedicine, the low fluorescence quantum yield of coumarin itself has not been fully understood so far. On the basis of our combined experimental and theoretical results we suggest a model for the ultrafast decay after photoexcitation incorporating two parallel radiationless relaxation pathways: one within the initially excited state via ring opening and the other one by transition into a dark state along the carbonyl stretching mode. The fluorescence quantum yield is determined by the position of the branching point relative to the Franck-Condon region which is strongly influenced by interactions with the environment and the substitution pattern. This model is finally capable of giving a comprehensive account of the striking differences observed in the photophysical behavior of coumarin as opposed to umbelliferone.
Gesehen am 28.10.2021